Food supplementation does not prevent oxidative stress in forager honey bees exposed to the fungicides bixafen, prothioconazole and trifloxystrobin - Freitas, Tainá Angelica de Lima [UNESP]; Alves, Thais Regina Ramos [UNESP]; Trivellato, Matheus Franco [UNESP]; Kato, Aline Yukari [UNESP]; Gomes, Cássia Regina de Avelar [UNESP]; Ferraz, Yara Martins Molina [UNESP]; Vicente, Eduardo Festozo [UNESP]; De Jong, David; Miranda, Camila Araújo [UNESP]; Mingatto, Fábio Erminio [UNESP]; Nicodemo, Daniel [UNESP] (My University, 2024)
As in other organisms, the antioxidant cellular defense system of bees helps maintain homeostasis. However, extrinsic factors such as pesticides and nutritional deficiencies can interfere. To determine whether nutritional supplementation can mitigate the oxidative damage caused by fungicides, five colonies were supplemented with sucrose syrup and a pollen-sucrose paste for 14 wk, while five other colonies were subjected to reduced protein intake due to the installation of pollen traps at hive entrances and were not given supplementary food. Following the food management period, forager bees were exposed by contact to 1 or 7 µg of a modern three component fungicide, or by its fungicide components, bixafen, prothioconazole, and trifloxystrobin, individually. After 24 h, treated and untreated control bees were dissected, and thorax homogenates were evaluated for signs of oxidative stress. Without fungicide treatment, food supplementation induced higher activity of the enzymatic antioxidants such as glutathione peroxidase and catalase, and altered the reduced glutathione to glutathione disulfide ratio. Increased malondialdehyde was detected in bees exposed to the three fungicides alone or in combination, except for trifloxystrobin at the lower dose, independent of nutritional condition. Food supplementation of honey bee colonies did not mitigate the oxidative stress caused by these fungicides in the bees.
Keywords: Antioxidant; Apis mellifera; dietary restriction; malondialdehyde; nutrition; pollen